Hyperbole in the Lyrics of Billie Eilish's "Birds Of A Feather" (2024) - Nur Kamalia, Semi Ningrat; Juanda, Juanda (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2024)
This research explores the use of hyperbole in Billie Eilish's song lyrics, specifically in "Birds of A Feather." lyrics Hyperbole, as a form of figurative language, is often used to amplify ideas or emotions through exaggerated expressions. The study aims to identify and analyze the hyperbolic elements within these lyrics and interpret their meanings using Claridge's (2011) theory of figurative language and Leech's (1981) theory of meaning. The lyrics were sourced from Genius and analyzed using a descriptive method focused on identifying and interpreting hyperbole. The findings reveal six significant instances of hyperbole, primarily conveying affective, connotative, and reflected meanings. The study underscores how hyperbole in Eilish's lyrics intensifies the emotional impact, creating vivid imagery and conveying deep feelings of love, loss, and despair. This research contributes to a broader understanding of rhetorical devices in music. Keywords: Hyperbole, Figurative Language, Song Lyrics